2008
DOI: 10.1590/s0021-75572008000300015
|View full text |Cite
|
Sign up to set email alerts
|

Doença pneumocócica invasiva em crianças e adolescentes soropositivos para HIV

Abstract: Objective: Invasive pneumococcal disease (IPD) primarily affects children less than 5 years old, the elderly and certain at-risk groups; especially people infected by the human immunodeficiency virus (HIV). The objective of this study was to analyze invasive pneumococcal diseases (IPD) in children and adolescents infected by the human immunodeficiency virus (HIV), with relation to morbidity, the case fatality ratio, pneumococcus serotypes, susceptibility to penicillin and ceftriaxone and to the proportion of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Na América Latina, o S. pneumoniae é o patógeno mais comum envolvido na pneumonia adquirida na comunidade, sendo responsável por 35% dos casos (Isturiz et al, 2010). A doença pneumocócica invasiva acomete principalmente crianças menores de 5 anos, idosos e indivíduos que se encontram em alguns grupos de risco (por exemplo, infectados pelo vírus da imunodeficiência humana -HIV) (Mattei et al, 2008).…”
Section: Introductionunclassified
“…Na América Latina, o S. pneumoniae é o patógeno mais comum envolvido na pneumonia adquirida na comunidade, sendo responsável por 35% dos casos (Isturiz et al, 2010). A doença pneumocócica invasiva acomete principalmente crianças menores de 5 anos, idosos e indivíduos que se encontram em alguns grupos de risco (por exemplo, infectados pelo vírus da imunodeficiência humana -HIV) (Mattei et al, 2008).…”
Section: Introductionunclassified
“…In a total of 100 samples, 15% resistance to penicillin, 1% resistance to cephalosporins -intermediate resistance in both cases -and no resistance to vancomycin was found. The risk factors for S. pneumoniae resistance are, mainly, the previous use of antibiotics and age inferior to one year of age 22 .A study executed byMattei et al (2008), observed that 19 children and adolescents infected with HIV and with invasive pneumococcal diseases -in which three cases were ABM -, 47.0% of the isolated S. pneumoniae strains from the CSF were not sensitive to penicillin, but all were sensitive to ceftriaxone. Of those resistant to penicillin, the most frequent serotype was 14.…”
mentioning
confidence: 99%
“…Of those resistant to penicillin, the most frequent serotype was 14. The elevated resistance rate to penicillin can be explained by the fact that the HIV infected patients were submitted to frequent antimicrobial treatments32 . The resistance to penicillin was restricted to the 6B, 19F, 23F, 14 and 19A serotypes, classically known as the pediatric serotypes, responsible for the elevated number of infections in children33 .In Brazil, the greatest incidence of ABM caused by S. pneumoniae was registered in infants with less than one year of age and bacterial resistance…”
mentioning
confidence: 99%